Neurosteroids Reduce Social Isolation-Induced Behavioral Deficits: A Proposed Link with Neurosteroid-Mediated Upregulation of BDNF Expression - Nin, Mauricio S.; Martinez, Luis; Pibiri, Fabio; Nelson, Marianela; Pinna, Graziano (Frontiers in Endocrinology, 2011)
The pharmacological action of SSRI antidepressants may include a normalization of the decreased brain levels of neurosteroids such as that of the progesterone metabolite allopregnanolone and that of the brain-derived neurotrophic factor (BDNF), which are decreased in patients with depression and PTSD. Allopregnanolone and BDNF decrease in these patients is associated with behavioral symptom severity. Antidepressant treatment upregulates both allopregnanolone levels and the expression of BDNF in a manner that significantly correlates with improved symptomatology, which suggests that neurosteroid biosynthesis and BDNF expression may be interrelated. Preclinical studies using the socially isolated mouse as an animal model of behavioral deficits that resemble some of the symptoms observed in PTSD patients have shown that fluoxetine and derivatives improve anxiety-like behavior, fear responses, and aggressive behavior by elevating the corticolimbic levels of allopregnanolone and BDNF mRNA expression. These actions appeared to be independent and more selective from the action of these drugs on 5-HT reuptake inhibition. Hence, this review addresses the hypothesis that in PTSD or depressed patients brain allopregnanolone levels and BDNF expression upregulation may be part of the mechanisms involved in the beneficial actions of antidepressants or other selective brain steroidogenic stimulant (SBSS) molecules.